Capacidade de mascaramento de resinas compostas para dentes clareados aplicadas pela técnica de estratificação - Dalmolin, Andressa (2020)
The present study assessed the masking ability of bleach-shade resin composites applied by multilayering technique placed over different substrates. The groups were divided according to the restorative system, different layering strategies, in two or three layers and shade of background. Disk-shape specimens of 1.5mm thickness were fabricated by cylindrical metallic matrices. Substrates with 2.0mm thickness were produced in opaque ceramic VITA simulating different shades of dental background (A2, A3, A3.5, C2, C3 and C4), and a bleached tooth (0M1). The color was measured by a reflectance spectrophotometer (SP60- X Rite). The masking ability was analyzed by total color difference between the specimens + substrates and, the coordinates of the 0M1 substrate, that were used as standard reference for CIEDE2000 equation. Data of ΔE00 were analyzed by one-way ANOVA and Tukey’s post-hoc test (p ≤ 0.05). The interpretation of effectiveness of the masking ability was based on the clinical perceptibility and acceptability thresholds. All tested groups presented ΔE values above the clinically acceptable threshold (ΔE00  1.8), regardless of the restorative system, layering strategy or color of the substrate. Multilayers over darker substrates showed greater color mismatch. The restorative systems of bleach-shade resin composites applied by layering technique were unable to ensure adequate masking of substrate of different colors.